Pengaruh Kualitas Layanan Onemart terhadap Minat Beli Siswa Kelas XI Bisnis Ritel SMK Negeri 1 Medan Tahun Ajar 2025/2026 - Nadya Rahmadhani; Yulie Aisyah Binrany; ⁠Sepania Tiarasi L Tobing; Daniel Martinus; Christian Putra Tarigan; Ivo Selvia Agusti (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2026)
This research aims to analyze the effect of service quality on students’ purchase intention at Onemart of SMK Negeri 1 Medan in the Academic Year 2025/2026. This study employed a quantitative approach using a survey method in which questionnaires were distributed to 60 students of the 11th grade Retail Business Department selected as the research sample. The research instrument was examined using validity and reliability tests, and the data were analyzed through normality test, multicollinearity test, heteroscedasticity test, simple linear regression, t-test, and coefficient of determination (R²) with the assistance of SPSS version 23. The findings indicate that service quality has a positive and significant effect on purchase intention, as reflected by the regression coefficient of 1.299, a significance value of 0.000 < 0.05, and a t-statistic value of 6.681 which exceeds the t-table value. The R Square value of 0.435 reveals that service quality contributes 43.5% to purchase intention, while the remaining 56.5% is influenced by other variables not examined in this research. Therefore, consistent improvement in service quality can increase students’ purchase intention toward Onemart.